The payment of church tithes by Serbs as a source of social conflict in medieval Hungary - Rokai, Peter (Balcanica Posnaniensia. Acta et studia, 2001)
The aim of the article is to analyze conflicts caused by the obligation of Orthodox Serbs settling in the Kingdom of Hungary during the fifteenth century to pay the church tithe. The author uses administrative records, ecclesiastical documents, and previous historiographical findings. The study demonstrates that, contrary to widespread opinion, a considerable proportion of Serbian peasants were required to pay tithes to the Catholic Church. This obligation led to disputes between Serbian settlers and ecclesiastical authorities, as well as between the clergy and landowners. The author also points to manifestations of passive resistance among Serbian peasants against such burdens. The conclusions emphasize that fiscal and religious issues played an important role in shaping social and ethnic relations within the multiethnic Kingdom of Hungary.